Investigation of the Role of Complementary Medicine on Anxiety of Patients Before and After Surgery: A Review Study. Issue 6 (November 2020) - Ebrahimi, Abed; Eslami, Jamshid; Darvishi, Isan; Momeni, Khadijeh; Akbarzadeh, Marzieh
Abstract : Every year millions of patients undergo surgery worldwide. Anxiety is a common pre- and postoperative problem. Nonpharmacologic anxiety control has been demonstrated to be more suitable in patients. The objective of this study was to apprise the evidence of the effect of various complementary therapies on pre- and postoperative anxiety among patients. A comprehensive literature search was made on Web of Science, Scopus, Cochrane, PubMed Irandoc, SID Science, ScienceDirect, Ovid, Mag Iran, and Google Scholar for original research studies published between 1980 and 2019. Original articles that reported the effect of complementary therapies in patients undergoing surgery were included. Ninety-six studies were analyzed. All of the studies have documented the effects of complementary therapies on improving pre- and postoperative outcomes of patients. Although methods varied considerably, most of the studies included in this review reported positive results. Therefore, there is some evidence that complementary therapies can lead to positive pre- and postoperative outcomes. Therefore, the efficiency and use of complementary medicine, along with the use of therapeutic techniques in classical medicine, can provide a new model for reducing anxiety before and after surgery. It is recommended that nurses conduct additional reviews or clinical studies so that effective approaches to integrated medical care can be developed and patients' health enhanced.